Effect of Methyl Jasmonate on the Performance of Tetranychus evansi Baker & Pritchard, 1960 (Acari: Tetranychidae) and Phytoseiulus longipes Evans, 1968 (Acari: Phytoseiidae) on Tomato Plants - Silva, Pauliana A.; Arce, Carla C. M.; Pallini, Angelo; Ataide, Livia M. S. (Entomological Communications, 2024)
Inducible anti-herbivore defenses in plants are predominantly regulated by jasmonic acid (JA). The red spider mite Tetranychus evansi Baker & Pritchard, 1960 (Acari: Tetranychidae) is an invasive pest known for its detrimental impact on tomato plants and other Solanaceae crops. Here, we investigated the extent to which T. evansi and the predatory mite Phytoseiulus longipes Evans, 1968 (Acari: Phytoseiidae) are affected by induced JA-defenses. Initially, we artificially induced the JA-response in tomato plants using exogenous methyl jasmonate (MeJA) and subsequently assessed the effect of JA defenses on spider mite by evaluating mortality and oviposition rates. Our findings revealed a higher mortality and lower oviposition rates on plants treated with MeJA compared to non-treated control plants. Furthermore, we examined the predatory mite’s predation rates on spider mite eggs produced on MeJA-treated and non-treated tomato plants. The results showed a reduced predation on T. evansi eggs derived from MeJA-treated plants, indicating a potential negative impact of JA-induced defenses on the predator’s performance. Finally, we released five predatory females on T. evansi-infested tomato plants treated and non-treated with MeJA, monitoring the predator population density for three generations. Predator population was not affected, as the abundance of larvae and adults was not significantly different between treatments. These findings underscore the negative impact of JA defenses on herbivores and highlight the trade-off it may pose on natural enemies.